Silicon carbide schottky diodes forward and reverse current properties upon fast electron radiation - M. Azim Khairi; Rosminazuin Ab. Rahim; Norazlina Saidin; Yusof Abdullah; Nurul Fadzlin Hasbullah (Bulletin of Electrical Engineering and Informatics, 2019)
This paper investigates on the reaction of 10 and 15MGy, 3MeV electron irradiation upon off-the-shelves (commercial) Silicon Carbide Schottky diodes from Infineon Technologies (model: IDH08SG60C) and STMicroelectronics (model: STPSC806). Such irradiation reduces the forward-bias current. The reduction is mainly due to the significant increase of the series resistance (i.e. Infineon: 1.45Ω at before irradiation → 121×103 Ω at 15MGy); STMicroelectronics: 1.44Ω at before irradiation → 2.1×109 Ω at 15MGy). This increase in series resistance gives 4.6 and 8.2 orders of magnitude reduction for the forward-bias current density of Infineon and STMicroelectronics respectively. It is also observed that the ideality factor and the saturation current of the diodes increases with increasing dose (i.e. ideality factor- Infineon: 1.01 at before irradiation → 1.05 at 15MGy; STMicroelectronics: 1.02 at before irradiation → 1.3 at 15MGy | saturation current- Infineon: 1.6×10-17A at before irradiation → 2.5×10-17A at 15MGy; STMicroelectronics: 2.4×10-15A at before irradiation → 8×10-15A at 15MGy). Reverse-bias leakage current density in model by Infineon increases by one order of magnitude after 15MGy irradiation, however, in model by STMicroelectronics decreases by one order of magnitude. Overall, for these particular samples studied, Infineon devices have shown to be better in quality and more radiation resistance toward electron irradiation in forward-bias operation while STMicroelectronics exhibit better characteristics in reverse-bias operation.